An Improved Hybrid PWM Technique for DC Capacitors Voltage Balance of Five Level DCMLI - Raju.K, Narasimha; Pavan.G, G.D.V. Sai; Harish.S, S.V.; R, Vignesh. (International Journal of Engineering and Technology, 2018)
The innate problem with five-level Diode Clamped Multi Level Inverter (DCMLI) is imbalance in supply DC capacitor voltages. This paper presents a novel Hybrid Pulse Width Modulation (PWM) technique to stabilize the capacitor voltages. The unbalance in capacitor voltages leads to decrement in inverter level, increase in switching stress and distortion in the output voltage. The existing solutions to this problem use either a back to back connection of inverter and rectifier or external dc sources for each capacitor, but there isn’t a solution which would inherently balance the capacitor voltages of five levels and above for DCMLI. To rectify this problem a novel hybrid PWM technique which is combination of Carrier based PWM (CBPWM) and Space Vector Modulation (SVM) is proposed. As per this technique conventional CBPWM is applied to meet the load demand and SVM is applied at certain selective intervals to balance the capacitors. The novelty lies in selection of appropriate switching state and the interval at which it must be applied to balance the capacitor voltages. This technique is simple to implement and gives rise to less switching losses.